In problem 3.3 b) of Schwartz's Quantum field theory you are asked to prove that $ Q = \int T_{00} d^3x $ is invariant under changing the Lagrangian $ \mathcal{L} \rightarrow \mathcal{L} + \partial_\mu X^\mu $ by a total derivative. In 3.3 a) I already wrote down the transformation of the stress-energy tensor $$ T_{\mu\nu} \rightarrow T_{\mu\nu} + \frac{\partial \left( \partial_\lambda X^\lambda \right)}{\partial \left( \partial_\mu \phi \right)} \partial_\nu \phi - g_{\mu\nu} \partial_\lambda X^\lambda $$

Plugging this into the formula for $Q$ you get $$ \delta Q = \int \frac{\partial \left(\partial_\lambda X^\lambda \right)}{\partial \dot{\phi}} \dot{\phi} - \partial_\lambda X^\lambda \, d^3x $$

From here I don't know how to proceed to show that $\delta Q = 0$. You could use the product rule with repsect to $\partial_t$ to then utilize the Euler-Lagrange equations to get $$ \delta Q= \int d^3x \, \partial_t \left(\frac{\partial \left(\partial_\lambda X^\lambda\right)}{\partial \dot{\phi}} \phi\right) + \phi \left(\frac{\partial \left(\partial_\lambda X^\lambda\right)}{\partial \phi}- \partial_i \frac{\partial \left(\partial_\lambda X^\lambda\right)}{\partial \left(\partial_i \phi\right)}\right) -\partial_\lambda X^\lambda,$$ but I don't see how this has helped me.

The solutions available online by To Chin Yu reads $$ \delta Q = \int \frac{\partial \left(\partial_\lambda X^\lambda \right)}{\partial \dot{\phi}} \dot{\phi} - \partial_\lambda X^\lambda \, d^3x \\ = -2 \int \partial_\lambda X^\lambda d^3x \\ = - 2 \partial_0 \int X^0d^3x \\ =0. $$ I understand the step from the second to the third equation where we have used $\int \partial_i X^i dx_i = X^i|_{\partial M} =0$ (no Einstein summation implied). But I don't see why the first line should be equal to the second line and why the third line should be zero.

If you can help me I would be most grateful :)


1 Answer 1


To get from the first line to the second, you integrate by parts underneath the integral sign. This is a classic technique used in many classical field theory problems. You would have had to do it already in (3.1) and (3.2), as I see it. You can always drop out the boundary term gained from the IBP, allowing you to change

\begin{equation} A \partial_{\mu} B = - (\partial_{\mu} A) B \end{equation} inside Lagrangians. You do the same here. Identify

\begin{equation} B =\partial_{\lambda} X^{\lambda}, \, \, A = \dot{\phi}, \end{equation} and make the switch (remembering that you are differentiating w.r.t $\dot{\phi}$), giving

\begin{align} &- \frac{\partial \dot{\phi}}{\partial \dot{\phi}} \partial_{\lambda} X^{\lambda} \\ &= - \partial_{\lambda} X^{\lambda} \end{align} This obviously combines with the other term, giving the factor of $-2$.

  • $\begingroup$ Thank you for your answer. Unfortunately, I don't see why partial integration should be allowed in the way you are describing it. The integral is with respect to $ d^3x $ and the derivative with respect to $ \dot{\phi} $. So one would need to show that the total derivative term $$ \frac{\partial}{\partial \dot{\phi}} \left( \dot{\phi} \partial_\lambda X^\lambda \right) $$ vanishes under the integral which I don't see obviously. Could you please clarify? $\endgroup$ Commented Nov 20, 2023 at 14:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.